Outcomes following autologous tumor tissue implantation with or without concurrent antineoplastic therapies in the treatment of sarcoids in 50 equids - Smith, Caitlin H.; Stewart, Holly L.; Stefanovski, Darko; Levine, David G. (Frontiers in Veterinary Science, 2025)
This study aimed to describe the effect of single implantation of autologous tumor tissue at inducing clinical regression of equine sarcoids. Special emphasis was placed on the influence of concurrent and subsequent therapies, time- independent outcomes, and associated complications. A retrospective review was conducted using medical records from the University of Pennsylvania’s New Bolton Center between May 2014 and January 2022. Follow-up data were collected through phone and email surveys. Descriptive statistics were generated, and outcomes were analyzed using univariate and multivariate logistic regression models. Fifty equids that underwent elective autologous tumor tissue implantation were included in the study. Complete resolution without recurrence was observed in 50% of cases. There was no significant difference in outcome between animals treated with autoimplantation alone and those receiving concurrent antineoplastic therapies. Equids with a history of treatment failure were 77% less likely to show improvement. After adjusting for other factors, sarcoids located on the body had 48% lower odds of clinical improvement, and each additional tumor decreased the odds of improvement by 11%. When tumor numbers decreased following initial implantation, the odds of recurrence were reduced by 71%. Two cases (4%) developed tumors at the implantation site. Autologous tumor implantation was most effective in animals with a lower tumor burden and was relatively less successful in cases involving body-localized sarcoids or tumors refractory to previous treatments. Severe complications were uncommon, and client satisfaction trended with incidence of recurrence. The technique is technically simple and may be beneficial in selected cases of equine sarcoids. Further research into the mechanisms may inform the development of future therapies, including potential commercial vaccines.